A Correlation between 3′-UTR of OXA1 Gene and Yeast Mitochondrial Translation - Maryam Hajikarimlou; Mohsen Hooshyar; Noor Sunba; Nazila Nazemof; Mohamed Taha Moutaoufik; Sadhena Phanse; Kamaledin B. Said; Mohan Babu; Martin Holcik; Bahram Samanfar; Myron Smith; Ashkan Golshani (Journal of Fungi, 2023)
Mitochondria possess their own DNA (mtDNA) and are capable of carrying out their transcription and translation. Although protein synthesis can take place in mitochondria, the majority of the proteins in mitochondria have nuclear origin. 3′ and 5′ untranslated regions of mRNAs (3′-UTR and 5′-UTR, respectively) are thought to play key roles in directing and regulating the activity of mitochondria mRNAs. Here we investigate the association between the presence of 3′-UTR from OXA1 gene on a prokaryotic reporter mRNA and mitochondrial translation in yeast. OXA1 is a nuclear gene that codes for mitochondrial inner membrane insertion protein and its 3′-UTR is shown to direct its mRNA toward mitochondria. It is not clear, however, if this mRNA may also be translated by mitochondria. In the current study, using a β-galactosidase reporter gene, we provide genetic evidence for a correlation between the presence of 3′-UTR of OXA1 on an mRNA and mitochondrial translation in yeast.